Partial substitution of commercial concentrate for Azolla filiculoides meal in the productive response of Oryctolagus cuniculus - Méndez-Martínez, Y.; Ramírez, J. L.; Álvarez, A. R.; Leyva, L.; Pérez, Y. (Cuban Journal of Agricultural Science, 2019)
In order to evaluate the effect of partial substitution of commercial concentrate (CC) for Azolla filiculoides (HA) meal in rabbit productive indicators (Oryctolagus cuniculus), a completely randomized design was used with 48 animals of 35 days old and mean weight of 646.3 ± 9.5 g. This study was carried out in Río Cauto municipality, Granma province, Cuba. Four treatments were used, consisting of 0, 6, 12 and 18% substitution of balanced feed for Azolla meal. Each treatment consisted of three replications and these with four experimental units in a simple classification design. Azolla meal showed 20.74 and 19.34 % of crude protein and fiber, respectively, as well as an adequate amino acid composition, highlighting methionine and leusin values of 14 and 38 g/kg CP, respectively. DM, CP and EM intake was superior for the commercial concentrate with 6,849 g, 1,205 g and 849.98 MJ/kg of DM, respectively. For the increase of liveweight, the best values belonged to the control treatment and to 12% of HA inclusion, with 2,276.11 and 2,258.78g, respectively. Something similar occurred for total mean gain with 27.32 g for CC and 27.05 g for the 12% inclusion treatment. Azolla meal has a suitable chemical composition to be used in the feeding of rabbits. The inclusion of up to 12% of this meal in the ration for rabbits did not affect the productive indicators evaluated. Key words: feeding, composition, conversion, gain, weight